1979
DOI: 10.1149/1.2129351
|View full text |Cite
|
Sign up to set email alerts
|

Thin Films—Interdiffusion and Reactions

Abstract: state materials that involve electronic conductivity. However, Chap. 7 does cover the electrochemistry of mixed ionic-electronic conduction where the electronic conductivity component can vary from very low to very high. An interesting formula index shows that halogen/oxide compounds are of dominant interest with particular emphasis on sodium aluminates and Compounds of copper, lithium, and silver. There is a good chapter on the theoretical aspects of solid electrolytes which sets the tone for the subsequent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(55 citation statements)
references
References 0 publications
2
53
0
Order By: Relevance
“…In our case, the dissociative form of adsorption dominates for the oxygen sensor working at temperatures of 700-900°C, and consequently, the adsorption isotherm differs from the linear Langmuir adsorption isotherm [35,36].…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…In our case, the dissociative form of adsorption dominates for the oxygen sensor working at temperatures of 700-900°C, and consequently, the adsorption isotherm differs from the linear Langmuir adsorption isotherm [35,36].…”
Section: Resultsmentioning
confidence: 74%
“…However, considering the assumptions to the mathematical model given above, these flows can be ignored [36].…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, we have made direct observation of the Pd,Si/Si( 1 11) epitaxial interface by means of HREM viewed on cross-sectional sFcimcns (Sheng and Chang 1976). The interface is rather wavy with a peak-to-peak distance of about 15nm.…”
mentioning
confidence: 90%
“…Some systematic research works on the properties and mechanism of silicide-silicon contacts have already been published (Poate, Tu and Mayer 1978, Tun& Poate, Bean, Gibson and Jacobson 1982). It has been shown that the structure of silicide-silicon epitaxial interfaces has great influence on the electrical properties of the contact.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8]). It is of interest to investigate the reaction and bonding of a Pb-free solder with various metals, such as nickel, which is widely used as a material for different applications, in microelectronic devices in particular [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%